Burden of tuberculosis in Eastern Africa region from 1990–2021: A systematic analysis for the Global Burden of Disease 2021 Study - Leltework Yismaw; Temesgen Zewotir; Essey Kebede Muluneh; Fentabil Getnet; Kerebih Getinet; Habtamu Abebe Getahun; Taye Abuhay Zewale; Mengistie Kassahun Tariku; Anemaw Asrat; Mulusew Andualem; Awoke Misganaw (PLoS ONE, 2025)
Background Tuberculosis (TB), despite being a preventable and curable disease, remains a leading infectious cause of death. In Eastern Africa, TB poses a significant public health challenge. This study examined TB incidence, prevalence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021. This study aims to provide evidence for policy and healthcare stakeholders in Eastern Africa. Method This analysis is part of the Global Burden of Disease (GBD) Study 2021 to estimate TB incidence, prevalence, TB-specific mortality, and DALYs. The GBD study applies several analytical tools and uses data from national health surveys, vital registration systems, WHO reports, and hospital records. The results were presented by age group, sex, location, and year, accounting for 95% uncertainty intervals. Result A significant decline was observed in TB burden across East African countries between 1990 and 2021. The age standardized TB incidence rate dropped by 53% (95% UI: 50.7%, 55.1%), from 518.8 per 100,000 in 1990–244 in 2021, while TB prevalence dropped by 29.1% (95% UI: 26.3%, 31.7%), from 38,577.6–27,366.1 per 100,000. TB-related deaths fell by 64.6% (95% UI: 55.0%, 71.4%), and TB related DALYs declined by 68.2% (95% UI: 60.3%, 73.6%). Despite these improvements, men consistently experienced higher TB incidence, prevalence, mortality, and DALYs compared to women. Ethiopia showed the highest reductions in terms of TB-related mortality and DALYs compared to countries in the region, with annual reduction rates of 6.0% and 6.6%, respectively. Conversely, Somalia had the highest TB burden in 2021 in terms of incidence, mortality, and DALYs. Mauritius and Seychelles maintained the lowest TB burden, attributed to strong health systems and socio-economic conditions. Conclusion A significant decline was observed in TB burden across eastern African countries between 1990 and 2021. However, TB rates remain significantly higher than global and African averages. Therefore, continued investment in health systems and tailored interventions is essential to alleviate the disease burdens, specifically in high-prevalence areas.